Who Goes on Disability when Times are Tough? The Role of Work Norms among Immigrants - Delia Furtado; Kerry L. Papps; Nikolaos Theodoropoulos (Global Labor Organization (GLO), 2020)
We examine how work norms affect Social Security Disability Insurance (SSDI) take-up rates in response to worsening economic conditions. By focusing on immigrants in the US, we can consider the influence of work norms in a person's home country, which we argue are exogenous to labor market prospects in the US. We find that the probability of receiving SSDI is more sensitive to economic downturns among immigrants from countries where people place less importance on work. We also provide evidence that this result is not driven by differential sensitivities to the business cycle or differences in SSDI eligibility.
Keywords: H55; J61; I18; J15; 330; Disability Insurance; Immigrants; Social Norms; Unemployment Rates